Critical Role of General Practitioners in Preventing Readmission Following Emergency Department Alcohol Screening and Brief Intervention Management of Alcohol-Related Problems - Simon Hazeldine; Imogen Davies; Robert J. Tait; John K. Olynyk (SAGE Publishing, 2021)
Introduction/Objectives: Alcohol screening and brief intervention (ASBI) strategies are useful in general practice (GP) but their effectiveness in the emergency department (ED) is unclear. We evaluated the effect of ED-based ASBI on re-admissions. Methods: 453 ED subjects exceeding the threshold score on the three-item Alcohol Use Disorders Identification Test-Consumption (females 3+: males 4+) were randomized. We conducted telephone follow-up at 1 and 3 months and recorded hospital events 6 months pre- and post-enrolment. Results: Median weekly alcohol use was 20 standard drinks (interquartile range (IQR) 9-45) on enrolment. After 3 months, 247 (55%) were able to be re-interviewed. Median alcohol use was 10 drinks (IQR 4-26). Six months later, subjects receiving ED-ASBI without GP follow-up had significantly greater risk of re-admission compared with those having GP follow-up (OR 1.68, 95%CI 1.06-2.65; P  = .028). Conclusions: ASBI reduces the likelihood of ED re-presentation only in subjects who have GP follow-up. The study has been registered as a clinical trial (Australian and New Zealand Clinical Trial Registry ACTRN12617001254381).